The relationship of environmental knowledge and environmental care attitude of students - Sasea, Louis Ivana; Ibrohim, Ibrohim; Sueb, Sueb (Inornatus: Biology Education Journal, 2023)
The environment as a place where living things live has undergone significant changes which have resulted in a decrease in environmental quality. The level of students' understanding and awareness of the environment greatly influences the existing environmental conditions. However, the fact is that environmental knowledge possessed by students has not been fully applied in their environment. This study aimed to ascertain the relationship between students' environmental knowledge and environmental attitudes. This study employed a survey method with a correlational design for its research. Class X MIPA students from SMA Negeri 1 Banyuputih comprised the entire study population. The technique of sampling employed isÂ saturated sampling. The data collection technique is by using a questionnaire on environmental knowledge and environmental attitudes which contains statements based on a Likert score. Students' environmental knowledge correlated with their environmental care attitude, with a Sig. 0.00 < 0.05.